Qur'anic instructions on abatement and control of environmental degradation: selected principles - Muhamad, Asmawati; Khan, Israr Ahmad; Ansari, Abdul Haseeb (Serials Publications, 2014)
Environmental degradation is a global threat that has a dynamic inter-play with socio-economic, institutional, and technological activities. Legal efforts are being made by all nations worldwide jointly and separately, but the problems are not yet under control. Technological solutions that we name as environmental friendly technologies, and that are extremely important, do not address the root causes of underlying political, social and economic factors. This serious threat has triggered scores of responses from the world religions to have discourse on developing framework and action plan to resolve this matter accordingly. As for Islam, it has clear paradigm and instruction on addressing environmental issues efficiently. Pertaining to this significant, this paper highlights three essential principles, i.e.the principle of trusteeship(amanah), justice (‘adl), and public interest (maslahah al- ‘ammah), which are derived from theQur’anic teachings on environmental wisdom. It is believed that proper education for imparting thesevalues at all levels can serve as constructive mechanism for abatement and control of environmental degradation successfully.